# Answer on Calculus Question for shasha

Question #42366

f(x) = x2 + 3; g(x)= square root x-2

Find f(g(x)).

Help me solve this please

Find f(g(x)).

Help me solve this please

Expert's answer

Let g(x)=sqrt(x-2)=y. (1)

We need to find f(y). So, we substitute (1) in f(y)=y^2+3:

f(g(x))=(sqrt(x-2))^2+3=x-2+3=x+1.

We need to find f(y). So, we substitute (1) in f(y)=y^2+3:

f(g(x))=(sqrt(x-2))^2+3=x-2+3=x+1.

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment